2014
DOI: 10.1016/j.physbeh.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induces neuroinflammation mediated by altered expression of the renin–angiotensin system in mouse forebrain nuclei

Abstract: Obesity is a widespread health concern that is associated with an increased prevalence of hypertension and cardiovascular disease. Both obesity and hypertension have independently been associated with increased levels of inflammatory cytokines and immune cells within specific brain regions, as well as increased activity of the renin-angiotensin system (RAS). To test the hypothesis that high-fat diet (HFD) induced obesity leads to an angiotensin-II (Ang-II)-dependent increase in inflammatory cells within specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 60 publications
(76 reference statements)
3
53
0
Order By: Relevance
“…The increased gene expression for RAS components and PICs were accompanied by increased microglial activation in the hypothalamus including the ARC, SFO and PVN. 32,34,35 Conversely, TNF-α upregulates LEPR-b protein level and cell surface expression, which can lead to an increased cellular response to leptin and soluble LEPR production in cultured cells. 15 These results suggest that in both the periphery and CNS, PICs also mediate the cardiovascular and metabolic effects of leptin.…”
Section: Discussionmentioning
confidence: 99%
“…The increased gene expression for RAS components and PICs were accompanied by increased microglial activation in the hypothalamus including the ARC, SFO and PVN. 32,34,35 Conversely, TNF-α upregulates LEPR-b protein level and cell surface expression, which can lead to an increased cellular response to leptin and soluble LEPR production in cultured cells. 15 These results suggest that in both the periphery and CNS, PICs also mediate the cardiovascular and metabolic effects of leptin.…”
Section: Discussionmentioning
confidence: 99%
“…29 TNF-α levels are increased in obesity and serve as a marker for obesity. 30 Recent studies have revealed that HFD feeding increases hypothalamic PIC expression including IL-1β, IL-6 and TNF-α, and several components of the RAS such as AT1-R. 14,31 The increased gene expression for the RAS and for PICs is accompanied by increased microglial activation in the hypothalamus including the arcuate nucleus (ARC), SFO and PVN. 13,32,33 Some of these responses were reversed upon deletion of AT1a specially within the PVN.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α) in both brain and peripheral tissues. 11,14,31,34 However, one recent study showed that in rats predisposed to DIO, the expression of proinflammatory biomarkers was increased in the mediobasal hypothalamus within 24 h of HFD onset, 13 suggesting that hypothalamic inflammation occurs prior to obesity onset. This raises questions as to what factor(s) or through which pathway HFD activates the CNS RAS and inflammation so that the brain is sensitized to circulating hypertensive agents in the initial stages of overnutrition before the advent of increased systemic inflammation and RAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Annette et al (de Kloet et al, 2014) reported the evidence that HFD induced obesity leads to angiotensin II (Ang-II) dependent increase in the inflammatory cells within specific fore brain regions related to cardiovascular regulation in adult male rats. They found that HFD consumption stimulated PVN and subfornical organ (SFO) of the hypothalamus which are related to energy balance similar to the arcuate nucleus, these centers initiates pro-inflammatory response that increase the expression of angiotensin type-Ia receptors (AT-Ia) which are necessary for energy balance.These receptors (AT-Ia) of SFO are impacted and regulated by levels of circulating factors that are regulated by adipocytes, for example, leptin increases SFO AT-Ia receptors expression (Hilzendeger et al, 2012).…”
Section: Renin-angiotensin System (Ras) Dependent Hypothalamic Inflammentioning
confidence: 99%
“…The PVN is found to be activated after high fat diet (de Kloet et al, 2014) and this resulted in activation of other pathways that intersect at the PVN leading to obesity related cardiovascular disease and inflammatory disease (Hill, 2012).…”
Section: Introductionmentioning
confidence: 99%